Dentoalveolar and Soft Tissue Compensation in Class III Malocclusion - Aws Ali Al-Kadhim H.; Nur Adila Khairuzzaman; Wan Nur Hafizah AB Halim; Azrul Hafiz Abdul Aziz (Japan international cultural exchange foundation a, 2024)
Indexed by ERA